Influence of a Sulphur Dioxide Active Storage System on the Quality of Ribes rubrum L. Berries - Luca Brondino; Davide Cadario; Nicole Roberta Giuggioli (Polish Journal of Food and Nutrition Sciences)
The aim of this study was to evaluate the post-harvest changes in the quality of red currants ( Ribes rubrum L.) cv. ‘Rovada’ after 60 days of storage under modified atmosphere packaging (MAP) conditions. The storage unit was a pallet, and two treatments were performed. The CO 2 -MAP treatment was used as a control, while the SO 2 -MAP treatment was CO 2 -MAP plus SO 2 . The initial gas composition was 15.0 kPa O 2 and 10.0 kPa CO 2 inside all MAPs, while SO 2 -generating active sheets were added to pellets in SO 2 -MAP treatment. Weight loss, total soluble solid content, titratable acidity, total phenolic and anthocyanin contents, antioxidant activity, microbial count, and visual and sensorial appearance were monitored after 30 and 60 days. The results showed that berries stored with SO 2 maintained the quality parameters for up to 60 days. Exposure to SO 2 was effective in controlling yeast evolution, reducing the population both at 30 and 60 days at one and two orders of magnitude, respectively. Red currants stored under SO 2 MAP obtained better visual quality score compared to CO 2 MAP-treated berries throughout storage. Active emitters of SO 2 , such as those proposed in this study, can be promising solutions to improve the post-harvest storage of red currants and the berries marketability.